Analysis of the Performance Evaluation Study of Generator Excitation Unit in Atik Bakery Factory - Kholaful Ahmad Harahap; Parlin Siagian; Haris Gunawan (Sean Institute, 2025)
Atik Bakery uses a power generation system to meet its operational energy needs, one of which comes from a generator unit that plays an important role in maintaining a stable power supply. One of the key components in generator operation is the excitation system that functions to regulate the generator output voltage. This study aims to evaluate the performance of the generator unit excitation system at Atik Bakery, by analyzing efficiency, voltage stability, and response to changes in load. The methods used include measuring the generator output voltage at various load conditions, as well as monitoring the parameters of the excitation system using measuring devices and data analysis. The results of the study indicate that the generator unit excitation system can maintain a stable output voltage under normal load conditions, but there is a decrease in performance at higher loads, which can affect the quality of power supply to the factory. This evaluation provides a basis for efforts to improve and enhance the performance of the excitation system to improve operational efficiency and stability at Atik Bakery.